Beyond steroids: clinical outcomes of intralesional low molecular weight heparin in the management of oral lichen planus: a case series - Sindhu, Simran Jeet; Gupta, Swati; Nagaraju, K.; Malik, Sangeeta; Singh, Supriya; Talwar, Aarti; Chaudhary, Komal (International Journal of Basic & Clinical Pharmacology, 2025)
The objective was to assess the clinical efficacy and safety of intralesional enoxaparin in symptomatic oral Lichen planus (OLP) management, coupled with a review of the literature. Ten patients with clinically and histopathologically diagnosed OLP were enrolled and treated with intralesional injections of enoxaparin (3 mg/ml) weekly for a period of eight weeks. Clinical parameters assessed were lesion type, pain according to the visual analogue scale (VAS), lesion severity according to the T-score, and quality of life (QoL) at both the initial visit and follow-up. Of the 10 patients included, the mean age was 40.0±17.78 years, with 60% female distribution, presenting most with erosive and reticular lesions in equal proportions. Outcomes revealed significant symptomatic improvement and clinical resolution, as highlighted by a sharp drop in VAS scores from 8.0 to 0.0, a drop in T-scores from 3.6 to 0.67, and an increase in QoL scores from 4.4 to 10.0, indicating complete resolution in daily functioning; there were no reported side effects. Weekly intralesional injections of enoxaparin are safe and represent an effective treatment modality in symptomatic OLP, improving pain symptoms, leading to resolution of lesions, and enhancing the QoL.